2010
DOI: 10.1111/j.1472-765x.2010.02899.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the colonization of sugarcane and rice plants by the endophytic diazotrophic bacterium Gluconacetobacter diazotrophicus marked with gfp and gusA reporter genes

Abstract: Aims:  To evaluate the colonization process of sugarcane plantlets and hydroponically grown rice seedlings by Gluconacetobacter diazotrophicus strain PAL5 marked with the gusA and gfp reporter genes. Methods and Results:  Sugarcane plantlets inoculated in vitro with PAL5 carrying the gfp::gusA plasmid pHRGFPGUS did not present green fluorescence, but β‐glucuronidase (GUS)‐stained bacteria could be observed inside sugarcane roots. To complement this existing inoculation methodology for micropropagated sugarcane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 18 publications
1
31
0
5
Order By: Relevance
“…Later, microscopy studies have also been extended to seed plants such as rice (Rouws et al 2010), which was also shown to be endophytically colonized. In fact, hydroponically grown rice seedlings have proven to be a valuable model system for G. diazotrophicus-plant interactions, allowing rapid assays and presenting low autofluorescence, which facilitates microscopy studies (Rouws et al 2010). However, the micropropagation technique is highly time consuming and laborious.…”
mentioning
confidence: 99%
“…Later, microscopy studies have also been extended to seed plants such as rice (Rouws et al 2010), which was also shown to be endophytically colonized. In fact, hydroponically grown rice seedlings have proven to be a valuable model system for G. diazotrophicus-plant interactions, allowing rapid assays and presenting low autofluorescence, which facilitates microscopy studies (Rouws et al 2010). However, the micropropagation technique is highly time consuming and laborious.…”
mentioning
confidence: 99%
“…Error bars represent the standard deviation. Significant differences between treatments are represented by asterisk (ANOVA,p<0.05) interaction between plants and bacteria isolated from grasses, including G. diazotrophicus (Rouws et al 2010;Meneses et al 2011;Alquéres et al 2013). In t h e c u r r e n t s t u d y, w e d e m o n s t r a t e d t h a t G. diazotrophicus endophytically colonizes A. thaliana roots and promotes plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…B. pseudomallei has been found in soil at levels of up to 10 5 CFU/g (6), so growth retardation in natural soils may not be as obvious or may allow persistent interactions between the plant and the microbe. The brevity of this experiment (7 days) and growth in Hoagland agar, although it is also commonly used (26,33,34), are not adequate for full rice growth and may not mimic growth in soil. It would be interesting to study B. pseudomallei-O.…”
Section: Discussionmentioning
confidence: 99%